Uji Efektivitas Program Intervensi 3E (Employability dan Entrepreneurship Enhancement) pada Mahasiswa Psikologi UKRIDA - Angela Elvanni Bemi; William Gunawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research discusses the effectiveness of the 3E Program which has just been implemented at the Faculty of Psychology, Krida Wacana Christian University (UKRIDA). This program is focused on students with the aim of explaining the development of career world 4.0, explaining strategies for developing mindset, attitude, skills and knowledge to increase student employability and entrepreneurship, motivating students to have high future employability and entrepreneurial intention so that students are ready to work and ready to become entrepreneurs. This research aims to determine whether there is a significant difference between students in increasing their perceived employability and entrepreneurship intention in the future after and before participating in the 3E intervention program. This research method is quasi-experiential using Hiebert Post-Pre. The research involved 88 active students of the Psychology Study Program at UKRIDA who were taking advanced career psychology courses, with participation dominated by female (79.5%) and male (20.5%) students. Researchers use measuring tools. The measuring tools used are the Perceived Future Employability Scale (PFES) by Matius & Gunawan (2022) and the Entrepreneurial Intention Scale which has been adapted to Indonesia by Abidin et al. (2020). The results of statistical analysis showed significant differences before and after the intervention, with the PFES t count of 15.608 (t ≥ 1.662) and EIS of 11.375 (t ≥ 1.662). This shows the success of the 3E Program in increasing students' views on employability and entrepreneurial intentions in the future. The conclusion states that this program is effective and can be a permanent step in supporting Psychology students at UKRIDA in determining career choices after completing their studies.